Thermal stress of Pseudomonas fluorescens in complex media. - McCoy, D R (1979)
Pseudomonas fluorescens (P7) cells were stressed by incubation at 43 degrees C for 2 h. The stress induced a 9-h lag in replication after the return of the temperature of the culture to 25 degrees C. Stressed cells demonstrated a sensitivity to diluents and plating media during the recovery period. Data from utilization of selective inhibitors suggested that ribonucleic acid and protein, but not deoxyribonucleic acid, syntheses were required for recovery by the cells. The cells lost uracil- and leucine-labeled material as a result of the stress, further suggesting that ribonucleic acid and protein damage had occurred. Membrane damage was indicated by sensitivity to sodium dodecyl sulfate near the end of the lag period. Membrane damage was also suggested by the failure of cells to incorporate labeled material from the recovery medium. The lesions induced in this foodlike system are compared with those previously reported for a minimal media model system (Gray et al., Appl. Microbiol. 26:78-85, 1973; Gray et al., Appl. Environ. Microbiol. 33:1074-1078, 1977).